Designing Multimodal Mobile Interaction for a Text Messaging Application for Visually Impaired Users - Duarte, Carlos; Desart, Simon; Costa, David; Dumas, Bruno (Frontiers in ICT, 2017)
While mobile devices have experienced important accessibility advances in the past years, people with visual impairments still face important barriers, especially in specific contexts when both their hands are not free to hold the mobile device, like when walking outside. By resorting to a multimodal combination of body based gestures and voice, we aim to achieve full hands and vision free interaction with mobile devices. In this paper, we describe this vision and present the design of a prototype, inspired by that vision, of a text messaging application. The paper also presents a user study where the suitability of the proposed approach was assessed, and a performance comparison between our prototype and existing SMS applications was conducted. Study participants received positively the prototype, which also supported better performance in tasks that involved text editing.